PERAN MEDIASI ASIMETRI INFORMASI DAN INSENTIF DALAM KASUS KESENJANGAN ANGGARAN PENDAPATAN ASLI DAERAH - Budi Barata Kusuma Utami; Rusdi Akbar (Optimum: Jurnal Ekonomi dan Pembangunan, 2020)
In the private sector budget slack are more dominant due to economic motivational factors such as incentives.In the local government sector there are organizations that operate as profit centers and can be assumed to be the same as the private sector.This study purpose to show empirical evidence about the mediation of information asymmetry and incentives in the phenomenon of budget slack in the Locally-Own Source Revenue Plan.Data collection techniques using primary data.The sample uses Echelon IIIa and IVa officials who work in local government institutions, namely the bureaucrats for collecting local revenue. This study results information asymmetry mediate tothe relationship of participation to budget slack.While incentives do not mediate to he relationship of information asymmetry to budget slack. Results of this study provides empirical evidence that economic factors arenot encourage of budget slack in the local government sector